2023
DOI: 10.1038/s41598-023-37054-8
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities associated with impulse control disorders in Parkinson’s Disease

Abstract: Impulse control disorders (ICDs) in Parkinson's disease (PD) are increasingly recognized as clinically significant non-motor features that potentially impair the quality of life. White matter hyperintensities (WMHs), detected by magnetic resonance imaging, are frequently observed in PD and can be associated with both motor- and certain non-motor symptoms. Given the limited number of non-motor features studied in this context, our aim was to reveal the potential association between the severity of WMHs and ICDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Multiple imaging studies have found that changes in brain structure, function, and metabolism prior to drug therapy in PD patients increase the risk of developing an ICD (Ray and Strafella, 2013;Aracil-Bolanos and Strafella, 2016;Mojtahed Zadeh et al, 2018;Santangelo et al, 2019;Baagil et al, 2023;Hernadi et al, 2023). Yoo et al (2015), using DTI technology, found that in the anterior corpus callosum, right internal capsule posterior limbs, right posterior cingulum, and right thalamic radiations, FA levels in the PD-ICD were significantly higher than in PD-non-ICD patients (corrected p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple imaging studies have found that changes in brain structure, function, and metabolism prior to drug therapy in PD patients increase the risk of developing an ICD (Ray and Strafella, 2013;Aracil-Bolanos and Strafella, 2016;Mojtahed Zadeh et al, 2018;Santangelo et al, 2019;Baagil et al, 2023;Hernadi et al, 2023). Yoo et al (2015), using DTI technology, found that in the anterior corpus callosum, right internal capsule posterior limbs, right posterior cingulum, and right thalamic radiations, FA levels in the PD-ICD were significantly higher than in PD-non-ICD patients (corrected p < 0.05).…”
Section: Discussionmentioning
confidence: 99%